Rainwater management and associated health risks: case study on the Welfengarten campus of the Leibniz University of Hannover, Germany - Carpio-Vallejo, Estefania; Düker, Urda; Nogueira, Regina (Frontiers in Water, 2025)
In the face of growing climate change challenges and increasing uncertainty over water availability, roof-harvested rainwater emerges as a promising alternative source in urban settings. At the Welfengarten campus, rainwater from the main building's roof feeds a pond that overflows into a park. However, concerns arise about potential waterborne diseases affecting children interacting with the pond. This study assessed the microbiological water quality of the urban pond and the associated health risks. Bi-monthly water sampling was conducted in 2020 and 2021, field observations documented interactions with the pond, and a microbial risk assessment quantified health risks from recreational exposure, addressing a critical gap in urban water safety research. Microbial analysis showed Total coliforms (4.41 × 101 to 2.42 × 103 MPN/100 mL), E. coli (5.20 × 100 to 4.61 × 102 MPN/100 mL), Enterococci (1.60 × 101 to 1.73 × 103 MPN/100 mL), Salmonella spp. (2.00 × 102 to 2.10 × 104 CFU/100 mL) and P. aeruginosa (4.00 × 100 to 6.00 × 103 MPN/100 mL). QMRA results showed maximum daily infection probabilities of 3.18 × 10−1 for Enterococci and 2.48 × 10−1 for Salmonella spp., exceeding the USEPA benchmark (3.60 × 10−2), while other bacteria remained below it. Given the lack of water quality guidelines for these environments, regular monitoring, particularly during summer, is recommended to safeguard public health and guide future water management policies.